Electrodeposition-flashing joul heat preparation of metal-doped co3o4 self-supporting electrode and its application

CN122959786APending Publication Date: 2026-10-23NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610709687.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-21
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

现有研究通过构建异质结构、引入缺陷及掺杂异质原子等策略,在一定程度上改善了钴基材料的电子结构并抑制其过度氧化,但这些方法仍存在一定局限性:一方面,传统过渡金属掺杂对钴的电子结构调控能力有限,难以在强酸性、高电位下实现长期稳定作用;另一方面,传统高温或溶剂热制备方法难以精确调控金属前驱体的成核与分散过程,易导致活性组分团聚或掺杂不均,从而影响催化剂结构均一性与活性位点利用效率

Benefits of technology

[0027]1、本发明提供的金属掺杂的Co3O4电催化剂通过向Co3O4中引入金属元素In、Al、Ga,其半满p轨道可与晶格氧的2p轨道发生强烈杂化,形成稳定的共价M-O键,从而实现对晶格氧反应活性的电子态调控。p-p轨道杂化不仅能够有效降低氧的2p能级,抑制其作为可脱离物种参与反应的能力,还能通过电子离域化抑制Co位点的过氧化行为,从根源上提升催化剂的结构稳定性和使用寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122959786A_ABST
    Figure CN122959786A_ABST
Patent Text Reader

Abstract

The application specifically relates to a metal-doped Co3O4 self-supporting electrode prepared by electrodeposition-flash evaporation of joule heat and application thereof, and belongs to the technical field of electrocatalysis. The metal-doped Co3O4 self-supporting electrode is synthesized on a conductive substrate by combining electrodeposition technology with flash evaporation of joule heat. By introducing metal elements In, Al and Ga, the half-full p orbits of the metal elements can be strongly hybridized with the 2p orbits of lattice oxygen, the 2p energy level of oxygen can be effectively reduced, the ability of oxygen as a detachable species to participate in the reaction can be inhibited, and the peroxidation behavior of Co sites can be inhibited through electron delocalization, so that the structural stability and service life of the catalyst are improved from the root. The application has the advantages of low cost, high efficiency, energy saving, and large-scale production, and has a guiding role for promoting the industrial application of PEM water electrolysis non-noble metal catalysts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrocatalysis technology and relates to an electrodeposition-flash Joule heating method for preparing metal-doped Co3O4 self-supporting electrodes and their applications. Background Technology

[0002] With societal development, the large-scale use of traditional fossil fuels has led to severe environmental pollution, making the development of clean and efficient green energy sources to replace them imperative. As the "dual carbon" goal is further advanced, green hydrogen production technologies have received widespread attention. Proton exchange membrane electrolysis (PEMWE) technology, due to its advantages such as high current density, high hydrogen purity, and fast response speed, has become an ideal choice for hydrogen production coupled with renewable energy. However, its anodic oxygen evolution reaction (OER) involves a four-electron transfer process, which is kineticly slow and currently relies mainly on precious metal-based catalysts such as iridium and ruthenium. The high cost severely restricts its large-scale application. Therefore, developing efficient, stable, and low-cost non-precious metal catalysts is crucial for the commercialization of PEMWE.

[0003] Spinel-type Co3O4-based catalysts are considered among the most promising non-noble metal OER catalysts due to their unique electronic structure and excellent intrinsic OER activity. However, pure Co3O4 exhibits poor stability in acidic environments, with Co ions readily dissolving, leading to rapid degradation of catalytic performance. Extensive research has been conducted on how to improve the activity and stability of Co3O4 in acidic oxygen evolution reactions. Existing studies have improved the electronic structure of cobalt-based materials and suppressed excessive oxidation to some extent through strategies such as constructing heterostructures, introducing defects, and doping with heteroatoms. However, these methods still have certain limitations: on the one hand, traditional transition metal doping has limited ability to regulate the electronic structure of cobalt, making it difficult to achieve long-term stability under strong acidity and high potential; on the other hand, traditional high-temperature or solvothermal preparation methods struggle to precisely control the nucleation and dispersion processes of metal precursors, easily leading to agglomeration or uneven doping of active components, thus affecting the uniformity of catalyst structure and the utilization efficiency of active sites.

[0004] A search of existing patent literature revealed that CN 119593005 A discloses a method for preparing a catalytic electrode by nitrate mixing, oscillating ball milling, and thermal decomposition. This method involves coating a nitrate mixture solution onto conductive carbon paper and then annealing to prepare a self-supporting electrode. However, this method is cumbersome and may result in uneven catalyst distribution. CN 119571388 A discloses a method for preparing a catalytic electrode by secondary impregnation and annealing. This method involves first impregnating a conductive carbon paper with a loaded dimethylimidazolium cobalt solution, then immersing it in a manganese salt solution to obtain a carbon cloth-loaded manganese-doped dimethylimidazolium cobalt, followed by annealing to obtain a carbon cloth-loaded cobalt-based oxide catalyst. However, this method is difficult to control the catalyst loading and has poor repeatability. CN 119194498 A discloses a method for preparing a catalytic electrode by thermal decomposition, involving adding a precursor solution to conductive carbon paper and then annealing. However, this method may result in poor dispersion of the precursor solution, affecting catalytic performance. Therefore, how to control the synthesis of highly efficient and stable non-precious metal catalysts is an urgent problem to be solved. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention provides a self-supporting metal-doped Co3O4 electrode prepared by electrodeposition-flash Joule heating and its application. This catalyst exhibits high efficiency and stability in oxygen evolution reaction (OER) in acidic reactions, and the material preparation method is highly efficient, energy-saving, and scalable, demonstrating potential for industrial application.

[0006] To achieve the above-mentioned objectives of the present invention, the specific technical solution adopted by the present invention is as follows:

[0007] In a first aspect, the present invention provides a metal-doped Co3O4 electrocatalyst, characterized in that the metal-doped Co3O4 catalyst is synthesized in situ on a conductive substrate by a combination of electrodeposition technology and flash Joule heat treatment.

[0008] As one embodiment of the present invention, the catalyst further includes a substrate on which metal-doped Co3O4 is supported, wherein the substrate is one of titanium felt, platinum-plated titanium felt, or FTO.

[0009] Secondly, the present invention also provides a method for preparing a metal-doped Co3O4 catalyst, comprising the following steps:

[0010] S1. Preparation of electroplating solution: Dissolve the cobalt source, doped metal source and complexing agent in deionized water and stir evenly to obtain the electroplating solution;

[0011] S2. Clean and dry the conductive substrate for pretreatment;

[0012] S3. Using the pretreated conductive substrate as the working electrode, the platinum sheet as the counter electrode, and the Ag / AgCl electrode as the reference electrode, electrodeposition is performed in the electroplating solution described in S1 under constant potential conditions to obtain hydroxide or hydroxy oxide precursors.

[0013] S4. The substrate with the precursor deposited in S3 is cleaned with deionized water and then vacuum dried.

[0014] S5. The dried sample is heat-treated in a flash Joule heating device to obtain the metal-doped Co3O4 self-supporting electrode.

[0015] As one embodiment of the present invention, the cobalt source in step S1 is any one of cobalt nitrate, cobalt chloride, and cobalt sulfate, more preferably cobalt nitrate.

[0016] As one embodiment of the present invention, the doping metal element in step S1 includes any one of In, Al, and Ga, and the metal source is any one of indium nitrate, indium sulfate, aluminum nitrate, aluminum sulfate, and gallium nitrate, more preferably a nitrate of the corresponding element.

[0017] As one embodiment of the present invention, the complexing agent in step S1 is one or more of sodium citrate, sodium tartrate, disodium ethylenediaminetetraacetate, and triethanolamine, more preferably sodium citrate.

[0018] In one embodiment of the present invention, in step S1, the solvent used for dissolution includes deionized water; in 40-60 mL of deionized water, the amount of cobalt nitrate is 1-2 mmol, the amount of the doping metal source is 0.05-0.1 mmol, and the amount of sodium citrate is 2-4 mmol. Preferably, in 40 mL of deionized water, the amount of cobalt nitrate is 2 mmol, the amount of the doping metal source is 0.1 mmol, and the amount of sodium citrate is 3 mmol.

[0019] In step S1 of this invention, the addition of a complexing agent can complex Co. 2+ By combining with doped metal ions to form stable complexes, the hydrolysis of Co is inhibited, thus achieving Co… 2+ Uniform co-deposition with doped metal ions reduces hydrogen evolution reaction.

[0020] In one embodiment of the present invention, in step S2, the conductive substrate is one of titanium felt, platinum-plated titanium felt, and FTO, more preferably platinum-plated titanium felt.

[0021] As one embodiment of the present invention, the cleaning in step S2 is to use acetone, anhydrous ethanol and deionized water to ultrasonically clean for 15 minutes each, and then blow dry with argon gas for later use.

[0022] In one embodiment of the present invention, the electrodeposition potential in step S3 is -1.0V vs. Ag / AgCl, and the deposition time is 15-30 min.

[0023] In one embodiment of the present invention, the temperature of the electroplating solution in step S3 is 30°C; stirring is performed during the deposition process to promote mass transfer, and the stirring speed is 150 rpm.

[0024] As one embodiment of the present invention, in step S4, the conductive substrate on which the precursor is deposited is washed four times with water and anhydrous ethanol and then dried in a vacuum oven at 60°C for 8 hours.

[0025] As one embodiment of the present invention, the flash Joule heating step in step S5 involves transferring the dried conductive substrate to the reaction chamber and evacuating it to a pressure of 10 Pa. Then, argon gas is used to purge the substrate to achieve a working pressure of 0.1 MPa. Finally, a DC voltage of 40 V is applied, and the discharge time is 200 ms, thereby achieving ultrafast synthesis of the catalyst on the conductive substrate.

[0026] Thirdly, this invention provides an electrode for preparing a metal-doped Co3O4 self-supporting electrode using electrodeposition-flash Joule heating and its application. Compared with the prior art, this invention has the following advantages:

[0027] 1. The metal-doped Co3O4 electrocatalyst provided by this invention introduces metal elements In, Al, and Ga into Co3O4. The half-filled p orbitals of these elements can strongly hybridize with the 2p orbitals of lattice oxygen, forming stable covalent MO bonds, thereby achieving electronic state modulation of the reactivity of lattice oxygen. This p-orbital hybridization not only effectively lowers the 2p energy level of oxygen, suppressing its ability to participate in reactions as a decoupled species, but also inhibits the peroxidation behavior of Co sites through electron delocalization, fundamentally improving the structural stability and lifespan of the catalyst.

[0028] 2. Compared to heat treatment methods, flash Joule heating, by applying millisecond-level high-intensity current, instantly raises the material to a high temperature, followed by rapid cooling. This helps stabilize the metastable structure, inhibits particle agglomeration or uneven growth, thereby achieving rapid reaction and material structure control. During the process, almost all electrical energy is converted into heat energy, with an energy utilization efficiency approaching 100%, significantly reducing energy consumption and carbon emissions.

[0029] 3. This invention uses a self-supporting method to directly load the catalyst onto a conductive substrate. Compared with powder catalysts used in industry, this reduces the coating process, eliminates the need for additional binders and conductive agents, effectively avoids catalyst agglomeration, and facilitates the transport of ions and electrons, which is suitable for the high current density operating conditions of PEM electrolyzers.

[0030] 4. This invention exhibits excellent catalytic performance in the acidic oxygen evolution reaction, with a current density of 10 mA / cm². 2 It requires a lower overpotential and can maintain long-term operation in a three-electrode system, exhibiting superior overall performance compared to similar Co3O4-based catalysts. Attached Figure Description

[0031] Other features, objects, and advantages of the present invention will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings:

[0032] Figure 1 The X-ray diffraction patterns of the catalysts prepared in Examples 1-3 and Comparative Example 1 of this invention are shown below.

[0033] Figure 2 This is a scanning electron microscope image from Embodiment 1 of the present invention;

[0034] Figure 3 The OER performance curves of Examples 1-3 and Comparative Example 1 of this invention are shown. The test environment is a three-electrode system, the electrolyte solution is 0.5M H2SO4, the platinum sheet is the counter electrode, and the Ag / AgCl electrode is the reference electrode.

[0035] Figure 4 The OER performance curves for Examples 1, 4, 5 and Comparative Example 1 of this invention are shown. The test environment was a three-electrode system, the electrolyte solution was 0.5M H2SO4, the platinum sheet was the counter electrode, and the Ag / AgCl electrode was the reference electrode.

[0036] Figure 5 Examples 1-3 and Comparative Example 1 of the present invention were performed at 10 mA / cm. 2 The stability curves at current density are shown. The test environment is a three-electrode system with a 0.5 M H2SO4 electrolyte solution, a platinum sheet as the counter electrode, and an Ag / AgCl electrode as the reference electrode. Detailed Implementation

[0037] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. The following embodiments will help those skilled in the art to further understand the present invention, but do not limit the present invention in any way. It should be noted that those skilled in the art can make several adjustments and improvements without departing from the concept of the present invention. These all fall within the protection scope of the present invention.

[0038] Example 1

[0039] This embodiment provides a method for preparing a self-supporting electrode with a 5% In-Co3O4 catalyst, including the following steps:

[0040] S1. Weigh 2 mmol of cobalt nitrate, 0.1 mmol of indium nitrate, and 3 mmol of sodium citrate and dissolve them in 40 mL of deionized water to prepare an electrolyte solution for later use.

[0041] S2. Cut the platinum-plated titanium felt (platinum layer thickness is 0.5μm) into 1*2cm pieces, and clean it with acetone, anhydrous ethanol and deionized water for 15min each in sequence. Dry it with argon gas and set it aside.

[0042] S3. Using the pretreated platinum-titanium felt from step S2 as the working electrode, a platinum sheet as the counter electrode, and an Ag / AgCl electrode as the reference electrode, electrodeposition is performed in the electroplating solution described in S1 under constant potential conditions. The deposition potential is -1.0V, and the deposition time is 20 minutes. The electroplating solution temperature is maintained at 30°C, and stirring is performed during the electroplating process to promote mass transfer at a stirring speed of 150 rpm. After electrodeposition, a layer of green precursor is observed deposited on the platinum-titanium felt. After rinsing four times with water and anhydrous ethanol, it is dried in a vacuum oven at 60°C for 8 hours.

[0043] S4. Transfer the dried platinum-plated titanium felt from step S3 to the flash evaporation Joule heating device, evacuate the reaction chamber to a pressure of 10 Pa, then purge with argon gas to achieve a working pressure of 0.1 MPa, and finally apply a DC voltage of 40 V for a discharge time of 200 ms to achieve ultrafast synthesis of the catalyst on a conductive substrate.

[0044] Example 2

[0045] This embodiment provides a method for preparing a self-supporting electrode with a 5% Al-Co3O4 catalyst, including the following steps:

[0046] S1. Weigh 2 mmol of cobalt nitrate, 0.1 mmol of aluminum nitrate, and 3 mmol of sodium citrate and dissolve them in 40 mL of deionized water to prepare an electrolyte solution for later use.

[0047] S2. Cut the platinum-plated titanium felt (platinum layer thickness is 0.5μm) into 1*2cm pieces, and clean it with acetone, anhydrous ethanol and deionized water for 15min each in sequence. Dry it with argon gas and set it aside.

[0048] S3. Using the pretreated platinum-titanium felt from step S2 as the working electrode, a platinum sheet as the counter electrode, and an Ag / AgCl electrode as the reference electrode, electrodeposition is performed in the electroplating solution described in S1 under constant potential conditions. The deposition potential is -1.0V, and the deposition time is 20 minutes. The electroplating solution temperature is maintained at 30°C, and stirring is performed during the electroplating process to promote mass transfer at a stirring speed of 150 rpm. After electrodeposition, a layer of green precursor is observed deposited on the platinum-titanium felt. After rinsing four times with water and anhydrous ethanol, it is dried in a vacuum oven at 60°C for 8 hours.

[0049] S4. Transfer the dried platinum-plated titanium felt from step S3 to the flash evaporation Joule heating device, evacuate the reaction chamber to a pressure of 10 Pa, then purge with argon gas to achieve a working pressure of 0.1 MPa, and finally apply a DC voltage of 40 V for a discharge time of 200 ms to achieve ultrafast synthesis of the catalyst on a conductive substrate.

[0050] Example 3

[0051] This embodiment provides a method for preparing a self-supporting electrode with a 5% Ga-Co3O4 catalyst, including the following steps:

[0052] S1. Weigh 2 mmol of cobalt nitrate, 0.1 mmol of gallium nitrate, and 3 mmol of sodium citrate and dissolve them in 40 mL of deionized water to prepare an electrolyte solution for later use.

[0053] S2. Cut the platinum-plated titanium felt (platinum layer thickness is 0.5μm) into 1*2cm pieces, and clean it with acetone, anhydrous ethanol and deionized water for 15min each in sequence. Dry it with argon gas and set it aside.

[0054] S3. Using the pretreated platinum-titanium felt from step S2 as the working electrode, a platinum sheet as the counter electrode, and an Ag / AgCl electrode as the reference electrode, electrodeposition is performed in the electroplating solution described in S1 under constant potential conditions. The deposition potential is -1.0V, and the deposition time is 20 minutes. The electroplating solution temperature is maintained at 30°C, and stirring is performed during the electroplating process to promote mass transfer at a stirring speed of 150 rpm. After electrodeposition, a layer of green precursor is observed deposited on the platinum-titanium felt. After rinsing four times with water and anhydrous ethanol, it is dried in a vacuum oven at 60°C for 8 hours.

[0055] S4. Transfer the dried platinum-plated titanium felt from step S3 to the flash evaporation Joule heating device, evacuate the reaction chamber to a pressure of 10 Pa, then purge with argon gas to achieve a working pressure of 0.1 MPa, and finally apply a DC voltage of 40 V for a discharge time of 200 ms to achieve ultrafast synthesis of the catalyst on a conductive substrate.

[0056] Example 4

[0057] This embodiment provides a method for preparing a self-supporting electrode with a 2% In-Co3O4 catalyst, including the following steps:

[0058] S1. Weigh 2 mmol of cobalt nitrate, 0.04 mmol of indium nitrate, and 3 mmol of sodium citrate and dissolve them in 40 mL of deionized water to prepare an electrolyte solution for later use.

[0059] S2. Cut the platinum-plated titanium felt (platinum layer thickness is 0.5μm) into 1*2cm pieces, and clean it with acetone, anhydrous ethanol and deionized water for 15min each in sequence. Dry it with argon gas and set it aside.

[0060] S3. Using the pretreated platinum-titanium felt from step S2 as the working electrode, a platinum sheet as the counter electrode, and an Ag / AgCl electrode as the reference electrode, electrodeposition is performed in the electroplating solution described in S1 under constant potential conditions. The deposition potential is -1.0V, and the deposition time is 20 minutes. The electroplating solution temperature is maintained at 30°C, and stirring is performed during the electroplating process to promote mass transfer at a stirring speed of 150 rpm. After electrodeposition, a layer of green precursor is observed deposited on the platinum-titanium felt. After rinsing four times with water and anhydrous ethanol, it is dried in a vacuum oven at 60°C for 8 hours.

[0061] S4. Transfer the dried platinum-plated titanium felt from step S3 to the flash evaporation Joule heating device, evacuate the reaction chamber to a pressure of 10 Pa, then purge with argon gas to achieve a working pressure of 0.1 MPa, and finally apply a DC voltage of 40 V for a discharge time of 200 ms to achieve ultrafast synthesis of the catalyst on a conductive substrate.

[0062] Example 5

[0063] This embodiment provides a method for preparing a self-supporting electrode with an 8% In-Co3O4 catalyst, including the following steps:

[0064] S1. Weigh 2 mmol of cobalt nitrate, 0.16 mmol of indium nitrate, and 3 mmol of sodium citrate and dissolve them in 40 mL of deionized water to prepare an electrolyte solution for later use.

[0065] S2. Cut the platinum-plated titanium felt (platinum layer thickness is 0.5μm) into 1*2cm pieces, and clean it with acetone, anhydrous ethanol and deionized water for 15min each in sequence. Dry it with argon gas and set it aside.

[0066] S3. Using the pretreated platinum-titanium felt from step S2 as the working electrode, a platinum sheet as the counter electrode, and an Ag / AgCl electrode as the reference electrode, electrodeposition is performed in the electroplating solution described in S1 under constant potential conditions. The deposition potential is -1.0V, and the deposition time is 20 minutes. The electroplating solution temperature is maintained at 30°C, and stirring is performed during the electroplating process to promote mass transfer at a stirring speed of 150 rpm. After electrodeposition, a layer of green precursor is observed deposited on the platinum-titanium felt. After rinsing four times with water and anhydrous ethanol, it is dried in a vacuum oven at 60°C for 8 hours.

[0067] S4. Transfer the dried platinum-plated titanium felt from step S3 to the flash evaporation Joule heating device, evacuate the reaction chamber to a pressure of 10 Pa, then purge with argon gas to achieve a working pressure of 0.1 MPa, and finally apply a DC voltage of 40 V for a discharge time of 200 ms to achieve ultrafast synthesis of the catalyst on a conductive substrate.

[0068] Comparative Example 1

[0069] This embodiment provides a method for preparing a self-supporting electrode based on a Co3O4 catalyst, comprising the following steps:

[0070] S1. Weigh 2 mmol of cobalt nitrate and 3 mmol of sodium citrate and dissolve them in 40 mL of deionized water to prepare an electrolyte solution for later use.

[0071] S2. Cut the platinum-plated titanium felt (platinum layer thickness is 0.5μm) into 1*2cm pieces, and clean it with acetone, anhydrous ethanol and deionized water for 15min each in sequence. Dry it with argon gas and set it aside.

[0072] S3. Using the pretreated platinum-titanium felt from step S2 as the working electrode, a platinum sheet as the counter electrode, and an Ag / AgCl electrode as the reference electrode, electrodeposition is performed in the electroplating solution described in S1 under constant potential conditions. The deposition potential is -1.0V, and the deposition time is 20 minutes. The electroplating solution temperature is maintained at 30°C, and stirring is performed during the electroplating process to promote mass transfer at a stirring speed of 150 rpm. After electrodeposition, a layer of green precursor is observed deposited on the platinum-titanium felt. After rinsing four times with water and anhydrous ethanol, it is dried in a vacuum oven at 60°C for 8 hours.

[0073] S4. Transfer the dried platinum-plated titanium felt from step S3 to the flash evaporation Joule heating device, evacuate the reaction chamber to a pressure of 10 Pa, then purge with argon gas to achieve a working pressure of 0.1 MPa, and finally apply a DC voltage of 40 V for a discharge time of 200 ms to achieve ultrafast synthesis of the catalyst on a conductive substrate. Performance testing

[0074] I. X-ray Diffraction Analysis

[0075] The catalysts prepared in Examples 1-3 and Comparative Example 1 were subjected to XRD analysis, and the results are as follows: Figure 1 As shown in the figure, all diffraction peaks before and after Co3O4 doping are highly consistent with the Co3O4 standard card (PDF#74-2120), with no additional peaks appearing, indicating that the catalysts are all spinel-type structures.

[0076] II. Scanning Electron Microscopy Analysis

[0077] The catalyst prepared in Example 1 was subjected to scanning electron microscopy analysis, and the results are as follows: Figure 2 As shown in the figure, the electrocatalytic material prepared by this invention exhibits a nanosheet structure with a large specific surface area and exposes more active sites.

[0078] III. OER Performance Testing

[0079] Test Methods: A conventional three-electrode system was used, with a platinum sheet as the counter electrode, an Ag / AgCl electrode as the reference electrode, and the prepared catalyst self-supporting electrode as the working electrode. Tests were performed on an Autolab electrochemical workstation. Prior to electrochemical measurements, the catalyst was stabilized in 0.5 mol / L H₂SO₄ solution within a potential range of 1 to 1.8 V for 15 cyclic voltammetry (CV) cycles to ensure stable performance. All polarization curves were recorded using linear sweep voltammetry (LSV) at a scan rate of 5 mV / s, with iR compensation correction applied.

[0080] The catalysts prepared in Examples 1-5 and Comparative Example 1 were subjected to OER performance tests, and the results are as follows: Figure 3 and Figure 4 As shown in the figure, the points are summarized in Table 1. It can be seen from the figure that the 5% In-Co3O4 prepared in Example 1 has a performance of 10 mA / cm². 2 The minimum overpotential was 299 mV, which is significantly lower than that of Co3O4 (410 mV), indicating that the catalyst prepared in this invention has good OER performance. Table 1 Example 1 299 Example 2 374 Example 3 357 Example 4 342 Example 5 359 Comparative Example 1 410

[0081] V. Stability Testing

[0082] Test Method: A conventional three-electrode system was used, with a platinum sheet as the counter electrode, an Ag / AgCl electrode as the reference electrode, and the prepared catalyst self-supporting electrode as the working electrode. Testing was conducted on a Koster electrochemical workstation. Prior to stability testing, the catalyst was activated by 20 cyclic voltammetric (CV) cycles in 0.5 mol / L H₂SO₄ solution within a potential range of 1 to 1.8 V, followed by activation at 10 mA / cm². 2 Chronopotential method test was performed at a current density of [value missing].

[0083] The catalysts of Examples 1-3 and Comparative Example 1 were in 0.5 mol / L H2SO4 at 10 mA / cm². 2 The stability curve at the current density is as follows Figure 5 As shown in the figure, metal doping improves the acidic OER stability of Co3O4. Among them, 5% In-Co3O4 exhibits the best stability at 10 mA / cm². 2 It can operate stably for more than 300 hours at the specified current density without significant degradation.

[0084] In summary, this invention employs electrodeposition combined with flash Joule heating to synthesize metal-doped Co3O4 self-supporting electrodes in situ on platinum-titanium felt. By introducing the metal elements In, Al, and Ga into Co3O4, its half-filled p orbitals can undergo strong hybridization with the 2p orbitals of lattice oxygen, forming stable covalent MO bonds, thereby achieving electronic state modulation of the reactivity of lattice oxygen. - p-orbital hybridization not only effectively lowers the 2p energy level of oxygen, suppressing its ability to participate in reactions as a decoupled species, but also inhibits the peroxidation behavior of Co sites through electron delocalization, fundamentally improving the structural stability and lifespan of the catalyst. A novel flash Joule heating technique is employed during the heat treatment process. By applying a millisecond-level high-intensity current to the platinum-titanium felt, the material is instantly raised to a high temperature, followed by rapid cooling. This helps stabilize the metastable structure, suppressing particle agglomeration or uneven growth, thereby achieving rapid reaction and material structure regulation. Almost all electrical energy is converted into heat energy during the process, with an energy utilization efficiency approaching 100%, significantly reducing energy consumption and carbon emissions. The catalyst prepared by this invention exhibits high efficiency and stability in oxygen evolution during acidic OER reactions. The material preparation method is highly efficient, energy-saving, and scalable, providing guidance for promoting the industrial application of non-precious metal catalysts for PEM water electrolysis.

[0085] The above descriptions are merely preferred embodiments and experimental examples of the present invention and are not intended to limit the scope of protection of the present invention. It should be understood that the present invention is not limited to the specific embodiments described above, and those skilled in the art can make various modifications and variations. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A metal element-doped Co3O4 electrocatalyst, characterized in that, Metal element-doped Co3O4 catalysts were synthesized in situ on a conductive substrate using electrodeposition technology combined with flash Joule heating technology.

2. The catalyst according to claim 1, characterized in that, The catalyst also includes a substrate on which Co3O4, a metal element doped, is supported. The substrate is one of titanium felt, platinum-plated titanium felt, or FTO.

3. A method for preparing a metal element-doped Co3O4 self-supporting electrode as described in claim 1 or 2, characterized in that, Includes the following steps: S1. Preparation of electroplating solution: Dissolve the cobalt source, doped metal source and complexing agent in deionized water and stir evenly to obtain the electroplating solution; S2. Clean and dry the conductive substrate for pretreatment; S3. Using the pretreated conductive substrate as the working electrode, the platinum sheet as the counter electrode, and the Ag / AgCl electrode as the reference electrode, electrodeposition is performed in the electroplating solution described in S1 under constant potential conditions to obtain hydroxide or hydroxy oxide precursors. S4. The conductive substrate with the precursor deposited in S3 is cleaned with deionized water and then vacuum dried. S5. The dried sample is heat-treated in a flash Joule heating device to obtain the metal element-doped Co3O4 self-supporting electrode.

4. As one embodiment of the present invention, the cobalt source in S1 is any one of cobalt nitrate, cobalt chloride, and cobalt sulfate; the doping metal includes any one of In, Al, and Ga, and the metal source is any one of indium nitrate, indium sulfate, aluminum nitrate, aluminum sulfate, and gallium nitrate; the complexing agent is any one of sodium citrate, sodium tartrate, disodium ethylenediaminetetraacetate, and triethanolamine.

5. As one embodiment of the present invention, in step S1, the solvent used for dissolution includes deionized water; in 40-60 mL of deionized water, the amount of cobalt source is 1-2 mmol, the amount of doped metal source is 0.05-0.1 mmol, and the amount of complexing agent is 2-4 mmol.

6. As one embodiment of the present invention, in step S2, the conductive substrate is one of titanium felt, platinum-plated titanium felt, and FTO. The cleaning step involves sequentially ultrasonically cleaning with acetone, anhydrous ethanol, and deionized water for 15 minutes each, followed by argon drying before use.

7. As one embodiment of the present invention, the electrodeposition potential in step S3 is -1.0V vs. Ag / AgCl, and the deposition time is 15-30 min. The temperature of the electroplating solution is 25-40℃; stirring is performed during the deposition process to promote mass transfer, and the stirring speed is 150 rpm.

8. As one embodiment of the present invention, in step S4, the conductive substrate on which the precursor is deposited is washed three times with water and anhydrous ethanol and then dried in a vacuum oven at 60°C for 8 hours.

9. As one embodiment of the present invention, the flash Joule heating step in step S5 involves transferring the dried conductive substrate to the reaction chamber and evacuating it to a pressure of 10 Pa, then purging it with argon gas to achieve a working pressure of 0.1 MPa, and finally applying a DC voltage of 40 V with a discharge time of 200 ms to achieve ultrafast synthesis of the catalyst on the conductive substrate.

10. The use of a metal-doped Co3O4 catalyst as described in any one of claims 1-9 in an acidic oxygen evolution reaction.

Citation Information

Patent Citations

  • Preparation method of metal atom doped cobaltosic oxide electrolyzed water catalyst

    CN119194498A

  • Cobalt-based oxide catalyst material and preparation method and application thereof

    CN119571388A